The Woodland Southeast - Anderson, David G., 1949-; Mainfort, Robert C., 1948- (University of Alabama Press, 2002)
This collection presents, for the first time, a much-needed synthesis of the major research themes and findings that characterize the Woodland Period in the southeastern United States. The Woodland Period (ca. 1200 B.C. to A.D. 1000) has been the subject of a great deal of archaeological research over the past 25 years. Researchers have learned that in this approximately 2000-year era the peoples of the Southeast experienced increasing sedentism, population growth, and organizational complexity. At the beginning of the period, people are assumed to have been living in small groups, loosely boun.